Health coaching for undergraduate nursing students: a pilot study for an action research - Romano, Rita; Begarani, Federica; Bignami, Elena Giovanna; Casubolo, Cristina; Corbara, Romina; La Sala, Rachele; La Torre, Pasquale; Marletta, Giuseppe; Marra, Sandrino; Martelli, Michele; Minari, Michele; Pelosi, Giulia; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The Nursing undergraduate degree educational program represents an intensive and complex course, and includes a number of professionalizing practical internships, and for these reasons it requires an action to support and improve. Coaching is based on the premise that people have personal strengths and abilities which, through a interview, can be directed to solving their problems. Several studies demonstrate the efficacy of Health Coaching in different University, but never have been measured benefits regard skills improving. The objective of the study is to assess the impact of a health coaching program on the nursing students. Method: A pre-post quasi-experimental study was conducted, involving the activation of a Health Coaching Program for 25 nursing students selected through convenience sampling, based on their fulfillment of the inclusion criteria. The Health Coaching Program was administered by the Health Coaching Academy. Result: This study also evaluated parameters such as: level of concentration in study, motivation, problem solving and reorganization skills, study organization skills, psycho-physical-emotional state comprehension, decision-making skills and self-esteem, noting a statistically significant increase post-HC program. A statistically significant improvement was also found in the students’ perception of their own stress management skills after the course. Conclusion: This study strengthens the hypothesis that HC programs contribute to improving performance of nursing students. Those conclusions need to be corroborated by future studies on the topic to further support the hypothesis that programs of HC within the learning nursing contexts can lead to a tangible benefit for students of the health professions.